Analisis Dampak Perubahan Metode Penilaian dalam Pengembangan Sumber Daya Manusia pada Kualiatas Kinerja Pegawai di Dinas Komunikasi dan Informatika Kota Jambi - Irawati Irawati; Zulfina Adriani; Hendriyaldi Hendriyaldi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the structural impact of changing performance appraisal methods within human resource development on the overall quality of employee performance at the Communication and Informatics Office (Diskominfo) of Jambi City. The research stems from a digital transformation paradigm, shifting from a conventional annual manual method to a periodic, digital-based assessment via the e-Kinerja application. To comprehensively understand the inner dynamics of this organizational transition, Kurt Lewin's Change Management Theory was employed as the core analytical framework, evaluating the transformation through three sequential phases: unfreezing, changing, and refreezing. Utilizing a descriptive qualitative approach, primary data were gathered through in-depth interviews with structural officials and implementing staff, complemented by secondary data from evaluation archives and regulations. The results indicate that the monthly digital appraisal exerts a significantly positive impact on performance quality, fostering higher work discipline, structured habits, and motivation among employees. However, the study identified five critical bottlenecks: low digital literacy among senior staff, server technical errors, inadequate onboarding socialization for new personnel, high digital documentation workloads, and fragile validation mechanisms regarding data authenticity. These systemic barriers suggest that the organizational change has not yet achieved a stable refreezing phase, thus requiring urgent strategic interventions in technological infrastructure and human resource governance.